Analysis of The Values of Moral Education in Nadzam Imrithy by Sheikh Syarafuddin Yahya Al-Imrithy - Muhammad Fodhil; Siti Hanifah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Moral education is the formation of good behavior that fosters moral values ​​to humans which will affect human behavior. In this 4.0 era, it is very important to form noble morals starting from early childhood, because we cannot deny that at this time there have been many cases played by early childhood such as being affected by the world of gadgets, disobeying parents, bullying to cases homicides committed by young children. Nadzam Al-imrithy is a book of nahwu which is very popular in the world of Islamic education. is a noble and monumental masterpiece of Imam Syarifuddin Yahya which contains 254 stanzas of nahwu knowledge. However, when examined more deeply, these nadzams also include moral values ​​that are related to everyday life. The problem that is discussed in this study is the values ​​of moral education contained in the implied meaning of nadzam al-imrithy by Sheikh Nerafudin and its actualization in the context of modern moral education. This research is literature, with the source nadzam al-imrithy. The data were collected from various literatures, with the method of tracking books, articles, internet, and magazines. The values ​​of moral education implied in nadzam al-imrithy consist of morals to Allah, morality to the Prophet, morality to oneself, morals of a student, morals of a teacher, morals towards society and the surrounding environment.